BLOCKCHAIN IN HR: NEW HORIZONS OF SECURITY AND TRANSPARENCY IN THE DIGITAL ECONOMY - CHERNYCHKO, Тetiana; STEHNEI, Marianna; PROSKURA, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Blockchain technology offers new horizons of security, transparency and efficiency in the digital economy. Its application can fundamentally change traditional approaches to recruiting, evaluating and managing employee data, and also affect the interaction with the workforce on a global level. For Ukraine, a country that is actively moving towards digitalization of public services and business processes, the problem of using blockchain in HR technologies is particularly relevant. In the conditions of the rapid development of the IT sector, the increase in the number of startups and the integration of Ukraine into the international market, blockchain can become a key tool for ensuring reliability, data security and the efficiency of personnel management. This will not only increase the competitiveness of Ukrainian companies, but also ensure transparency and openness in HR processes, contributing to the creation of trust between employees and employers.The purpose of the article is a comprehensive analysis of the potential of using blockchain technologies in the field of human resources (HR) management with an emphasis on solving key challenges related to ensuring the security, reliability of data and the effectiveness of HR processes in the conditions of martial law in Ukraine.The research uses a comprehensive approach, which includes the analysis of scientific publications, articles, monographs and reports at conferences on blockchain and human resource management, as well as a comparative analysis of cases of using blockchain technologies in HR practices.The article seeks to determine how blockchain can contribute to the optimization of work processes, the protection of personal data of employees and the maintenance of operational stability of relocated enterprises, as well as to discuss potential obstacles and limitations in the integration of blockchain into HR systems. Particular attention is paid to the analysis of research and development of domestic and foreign scientists in this field, with the aim of determining promising directions for further research and developing practical recommendations for the effective implementation of blockchain technologies in HR practice in Ukraine.Blockchain can transform traditional approaches to human resource management, making processes more efficient, secure, and fair. However, for the full implementation of these practices, a number of technical, legal and organizational challenges need to be overcome, which outlines the prospects for further research.
Keywords: digital economy; HR technologies; blockchain; digital transformation